The Smart City Concept in the 21st Century - Eremia, Mircea; Toma, Lucian; Sanduleac, Mihai (Procedia engineering, 2017)
The quality of life was significantly improved in the last century mainly as regards the access to services. However, the heavy industrialization and the increasing population in the urban areas has been a big challenge for administrators, architects and urban planners. This paper provides a brief presentation of the evolution of the “smart city” term and the most representative characteristics of it. Furthermore, various alternative terms that were proposed to describe the multiple characteristics of the future cities are analyzed. A connection between smart city and smart grid is also presented.